TWO NEW SPECIES OF THE GENUS JAURAVIA MOTS. FROM INDIA (COLEOPTERA : COCCINELLIDAE : STICHOLOTIDINAE) - SINGH, V.K.; SINGH, DEVINDER (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2013)
Two new species viz. Jauravia bicaullatus sp. nov. and J. punjabensis sp.nov. are described from Tamilnadu and Punjab, respectively. The genus is a first report form Punjab even North West India.